Numerical Investigation into the Effect of Blade Trailing-Edge Thickness on the Performance of Axial Fans - Maciej MAJCHER (Numeryczna analiza wpływu grubości krawędzi spływu łopatki na charakterystyki wentylatorów osiowych, 2018)
This paper presents the results of a numerical investigation into the effect of blade trailing-edge thickness and shape on the performance of a rotor ring model of axial fan. The numerical simulations carried out under this investigation provided the performance characteristics of efficiency, working medium power, and total pressure increase in the function of the volumetric flow rate of the rotor ring. The investigated blade trailing-edge thickness values were 1 mm, 2 mm, and 3 mm. The models for the simulation series were developed with rounded and sharp blade trailing edges, for all thickness values thereof. The rounded trailing blade edges were modelled in the form of an arc over which the conditions of tangency with the upper and lower contours of the airfoil were imposed. The blades of the modelled blade fan were designed with the NACA 65-810 airfoil. To verify the applied turbulence model and mesh settings, experimental tests of the model rotor ring were performed on an axial fan test bed. \ The obtained experimental data was compared with numerical results. The results showed a significant impact of the thickness and shape of the blade trailing edge on the performance characteristics of axial fans.
Keywords: Eksploatacja wentylatorów osiowych